PENINGKATAN AKTIFITAS DAN MOTIVASI MAHASISWA DALAM PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN HANDOUT - Maharani Putri; Ance Jusmaya; Okma Permata (Ensiklopedia of Journal, 2025)
Abstract: This study aims to improve students' engagement and motivation in learning English through the use of handout media. The research was conducted on students of the Accounting Study Program, Class of 2023/2024, at Universitas Sumatera Barat. The method used was Classroom Action Research (CAR), which consisted of two cycles. The results showed that the use of handouts significantly increased students' positive engagement and reduced negative behaviors during learning. Learning mastery also improved from 63% to 96%. These findings indicate that handouts are an effective learning aid in teaching English at the university level.Keywords: Learning Activity, Motivation, Handout, English, Students